ENTAILMENT AND IMPLICATURE IN THE LANGUAGE OF ADVERTISING - Eneng Uswatun Hasanah (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2014)
Language plays an important role in life. It is not only used as a mean of communication and selfexpression but also to influence people. This study discusses hidden meaning of nine slogans used in advertisements. This qualitative research finds out that the entailment meaning of advertisement slogans analyzed are different to their implicative meaning. The respondents tend to believe in implicative meaning because it is more promising and persuasive.